ENVIRONMENTAL COSTS AND THEIR ROLE IN MEASURING & IMPROVING THE ENVIRONMENTAL STATUS OF INDUSTRIAL COMPANIES AN APPLIED RESEARCH IN SOUTH CEMENT FACTORY - AL-MUTHANNA GOVERNORATE - Basim Mohammed Merhej, Prof. Dr. Saoud Chayed Mashkour, Dr. Mohammed Sameer Dherib AL Robaaiy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The environmental responsibility of industrial companies is one of the biggest challenges facing the economic, financial and social systems of countries and regional and international organizations, as the high volume of industrial activities directly affects environmental pollution that includes (air, water, land, biological diversity, waste, radiation, chemicals, and noise), which leads to an imbalance of the components and elements of the environmental system. The study aims to study the effect of measuring environmental costs on determining a clearly defined strategy of environmental responsibility for industrial companies; as well as directing attention to the environmental impacts caused by industrial companies as a result of their industrial activity, which these companies must make more efforts to reduce the level of environmental pollution risks in order to achieve the goal of achieving environmental responsibility. This research was conducted in the Cement Factory - South Sammawa located in the city of Sammawa - Governorate of Al-Muthanna - Iraq, through studying the factory data and reports for the year 2014, and according to the desire of the factory management for determining the environmental responsibility. The study reached the conclusions that were most prominent, that the concept of environmental responsibility is that all the obligations and activities performed by industrial companies towards the internal and external environment to reduce the risks of environmental pollution, must be adhered to and develop a strategy of environmental responsibility based on building models and methods used in measuring costs environmental, and define these obligations from the financial and non-financial side for the purpose of reporting them in the financial reports and statements and communicating them to the relevant authorities and stakeholders for the purpose of taking appropriate decisions. The study recommended that industrial companies should be taken into consideration the process of measuring environmental costs in order to implement the strategy of sustainable environmental responsibility and disclose it in their reports and financial statements issued annually for the purpose of knowing the amount of spending on environmental responsibility and their contribution to addressing environmental problems that are reflected in achieving the elements of sustainable development in Country .